Hubungan Faktor Sosial-Ekonomi dengan Preferensi Konsumen pada Buah Apel Red Delicious di Supermarket Yogyakarta - Kismantoroadji, Teguh (Caraka Tani: Journal of Sustainable Agriculture, 2007)
The aim of the research was study to the effect of kind of the economic-social factor and the consumer preferences and their interaction on available delight of the red delicious apel fruits. The result showed that both kind of influence available interaction significant on the age with the consumer preferences of the flavor and delicious to pay for the Red delicious, and not significantly on the age with the consumer preferences of the color and size. Beside its, the result showed no significant on the schoolwork with the consumer preferences of the flavor to pay for the Red delicious but the salary of consumers with the size, color and delicious the Red delicious both have interection significant